2023
DOI: 10.3389/fncel.2023.1247761
|View full text |Cite
|
Sign up to set email alerts
|

AQP4-independent TRPV4 modulation of plasma membrane water permeability

Barbara Barile,
Maria Grazia Mola,
Francesco Formaggio
et al.

Abstract: Despite of the major role of aquaporin (AQP) water channels in controlling transmembrane water fluxes, alternative ways for modulating water permeation have been proposed. In the Central Nervous System (CNS), Aquaporin-4 (AQP4) is reported to be functionally coupled with the calcium-channel Transient-Receptor Potential Vanilloid member-4 (TRPV4), which is controversially involved in cell volume regulation mechanisms and water transport dynamics. The present work aims to investigate the selective role of TRPV4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…Our results showed that deletion of AQP4 does not affect astrocyte swelling under hypoosmotic stress. This result is not surprising, because it agrees with the results of Murphy et al (2017) , Barile et al (2023) , who reported that the swelling of astrocytes does not require AQP4. Similarly, Mola et al (2016) showed that cells lacking AQP4 can swell, albeit more slowly, but are unable to trigger the RVD.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that deletion of AQP4 does not affect astrocyte swelling under hypoosmotic stress. This result is not surprising, because it agrees with the results of Murphy et al (2017) , Barile et al (2023) , who reported that the swelling of astrocytes does not require AQP4. Similarly, Mola et al (2016) showed that cells lacking AQP4 can swell, albeit more slowly, but are unable to trigger the RVD.…”
Section: Discussionsupporting
confidence: 91%
“…4 & 5) and pressure-evoked current (Yarishkin, Phuong et al 2021) are consistent with time-dependent formation of EET messenger molecules (Vriens, Watanabe et al 2004, Ryskamp, Frye et al 2016). TRPV4-mediated osmosensing has been associated with the promotion of cell swelling and RVD (Becker, Blase et al 2005, Hoffmann, Lambert et al 2009, Jo, Ryskamp et al 2015, Barile, Mola et al 2023. The suppression of the amplitude of HTS-induced swelling by HC-06 and stimulation of cell volume expansion by GSK101 under isotonic conditions suggest that, as reported recently for glial cells (Jo, Ryskamp et al 2015, Mola, Sparaneo et al 2016, Barile, Mola et al 2023 TRPV4 activity promotes cell swelling instead of time-dependent volume regulation.…”
Section: Discussionmentioning
confidence: 84%
“…Given that (i) TRPV4 inhibition, knockdown and Ca 2+ chelation suppress HTS-induced swelling (Fig. 2) (Jo, Ryskamp et al 2015) and (ii) swelling is augmented in cells that overexpress TRPV4 (Barile, Mola et al 2023), AQPs may not be required to facilitate cell swelling in response TRPV4-mediated Ca 2+ influx. NKCC1 transports water (Zeuthen and MacAulay 2002) and may modulate outflow resistance (Al-Aswad, Gong et al 1999) whereas TRPM4 shows strong expression in mouse and human TM and mediates 9-phenanthrol-sensitive Na + influx in GSK101-stimulated pTM cells (Yarishkin, Phuong et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AQP4 is known to be functionally and structurally associated with the volume-and thermosensitive calcium channel transient receptor potential vanilloid member-4 (TRPV4), which is also implicated in mechanisms regulating water transport and calcium homeostasis, the detection of changes in cell volume, and possibly, its regulation [144][145][146][147]. In vitro studies relating to Aqp4 -/astrocytes revealed that the possible role of TRPV4 is to tune plasma membrane water permeability and protect against severe osmotic challenges due to fast AQP4-dependent water transport [146]. However, the role of TRPV4 and calcium influx from extracellular space in the regulation of cell volume is controversial, and there is evidence that TRPV4 is not essential for regulatory volume decreases after AQP4-mediated cell swelling [145,147].…”
Section: Aqp4 and Cns Homeostasismentioning
confidence: 99%